2014
DOI: 10.1002/mds.25858
|View full text |Cite
|
Sign up to set email alerts
|

Study of medication‐free children with Tourette syndrome do not show imaging abnormalities

Abstract: Analyses revealed no differences between controls and patients with TS in gray or white matter. Possible discrepancies between cohorts and methods may play a role in the different findings in other studies. Further studies investigating well-defined cohorts with TS analyzing both gray and white matter in the same cohort may add additional information to the pathophysiology of TS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…Although both TD and ADHD have been previously associated with volume alterations in the BG, the literature to date is heterogeneous. The current null findings replicate in a larger sample a small number of studies that found no associations between BG nuclei volume and TD (n = 13‐38) and no association between either TD or ADHD and BG nuclei volumes (n = 14‐37) in children. Furthermore, consistent with previous findings in children, the current study also found no asymmetry abnormalities associated with TD .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although both TD and ADHD have been previously associated with volume alterations in the BG, the literature to date is heterogeneous. The current null findings replicate in a larger sample a small number of studies that found no associations between BG nuclei volume and TD (n = 13‐38) and no association between either TD or ADHD and BG nuclei volumes (n = 14‐37) in children. Furthermore, consistent with previous findings in children, the current study also found no asymmetry abnormalities associated with TD .…”
Section: Discussionsupporting
confidence: 74%
“…However, the literature of TD and ADHD neuroimaging research is inconsistent, and determining whether BG structural abnormalities are unique or common to the respective disorders is difficult because few studies have examined groups with TD and ADHD together in 1 study. Furthermore, those studies have been underpowered and inconsistent in their findings …”
mentioning
confidence: 99%
“…In this study, we combined TBSS and atlas‐based ROI analysis to examine both superficial and DWM structural and microstructural changes in TS patients with short disease duration without OCD. We found widespread structural alterations in TS children brain using both methods while a previous study [Jeppesen et al, ] selected seven ROIs on the WM skeleton and found no difference between controls and TS patients in these regions corrected for multiple comparisons with Bonferroni method. The discrepancies of study subjects, analysis method to derive the statistical result and multiple comparisons correction method may play a role in the different findings resulting from both studies.…”
Section: Discussionmentioning
confidence: 45%
“…Since then, a number of studies have investigated anatomical structure in TS, implementing structural brain measures such as volumetry, cortical thickness, and diffusion (fractional anisotropy, mean diffusivity, etc.). This line of research has continued in the past year, finding differences between TS and control groups in cortical gray matter volume [6], subcortical gray matter volume [7], and diffusivity of cortical and subcortical regions [7, 8]. …”
Section: A Focus On Anatomymentioning
confidence: 99%
“…and probabilistic tractography. Several recent studies in TS have examined diffusivity measures to investigate microstructural alterations in white matter [8, 13, 14] and probabilistic tractography to study the integrity of connections between regions [13, 15]. …”
Section: Structural Connectivitymentioning
confidence: 99%